Human dendritic cell interactions with the zoonotic parasite Cryptosporidium parvum result in activation and maturation - Ross, Ralf; Hasheminasab, Seyed Sajjad; Conejeros, Iván; Gärtner, Ulrich; Kamena, Faustin; Krueger, Andreas; Taubert, Anja; Hermosilla, Carlos (Frontiers in Immunology, 2024)
Cryptosporidiosis in humans is caused by infection of the zoonotic apicomplexan parasite Cryptosporidium parvum. In 2006, it was included by the World Health Organization (WHO) in the group of the most neglected poverty-related diseases. It is characterized by enteritis accompanied by profuse catarrhalic diarrhea with high morbidity and mortality, especially in children of developing countries under the age of 5 years and in HIV patients. The vulnerability of HIV patients indicates that a robust adaptive immune response is required to successfully fight this parasite. Little is known, however, about the adaptive immune response against C. parvum. To have an insight into the early events of the adaptive immune response, we generated primary human dendritic cells (DCs) from monocytes of healthy blood donors and exposed them to C. parvum oocysts and sporozoites in vitro. DCs are equipped with numerous receptors that detect microbial molecules and alarm signals. If stimulation is strong enough, an essential maturation process turns DCs into unique activators of naïve T cells, a prerequisite of any adaptive immune response. Parasite exposure highly induced the production of the pro-inflammatory cytokines/chemokines interleukin (IL)-6 and IL-8 in DCs. Moreover, antigen-presenting molecules (HLA-DR and CD1a), maturation markers, and costimulatory molecules required for T-cell stimulation (CD83, CD40, and CD86) and adhesion molecules (CD11b and CD58) were all upregulated. In addition, parasite-exposed human DCs showed enhanced cell adherence, increased mobility, and a boosted but time-limited phagocytosis of C. parvum oocysts and sporozoites, representing other prerequisites for antigen presentation. Unlike several other microbial stimuli, C. parvum exposure rather led to increased oxidative consumption rates (OCRs) than extracellular acidification rates (ECARs) in DCs, indicating that different metabolic pathways were used to provide energy for DC activation. Taken together, C. parvum-exposed human DCs showed all hallmarks of successful maturation, enabling them to mount an effective adaptive immune response.